2003
DOI: 10.1038/sj.bjc.6601043
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of temozolamide (TMZ) combined with procarbazine (PCB) in patients with gliomas

Abstract: Temozolomide (TMZ) is an oral alkylating agent with a good safety profile and proven efficacy in the treatment of malignant glioma. Procarbazine (PCB) has been used for treating gliomas for many years and here both agents were combined in the treatment. This phase I study was designed to evaluate the efficacy and safety of TMZ alone (course 1) and TMZ in combination with PCB in subsequent courses in chemotherapy-naïve patients with malignant glioma. Patients with anaplastic astrocytoma (AA), glioblastoma multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…One of the most potent agents, O 6 -benzylguanine, has been investigated in combination with TMZ in a couple of phase I studies with evidence of activity against refractory malignant gliomas (45,46). Similarly, clinical trials to evaluate the activity of procarbazine or cisplatin combined with TMZ have been conducted in patients with recurrent GBM (47,48). Whether these approaches can overcome resistance to TMZ through downregulation of MGMT activity needs to be verified in comparison with the standard TMZ regimen in patients with GBM having high MGMT expression.…”
mentioning
confidence: 99%
“…One of the most potent agents, O 6 -benzylguanine, has been investigated in combination with TMZ in a couple of phase I studies with evidence of activity against refractory malignant gliomas (45,46). Similarly, clinical trials to evaluate the activity of procarbazine or cisplatin combined with TMZ have been conducted in patients with recurrent GBM (47,48). Whether these approaches can overcome resistance to TMZ through downregulation of MGMT activity needs to be verified in comparison with the standard TMZ regimen in patients with GBM having high MGMT expression.…”
mentioning
confidence: 99%
“…The toxic effects Grade 3 and 4 lymphocytopenia have been observed in most studies [19,35,37,44] with incidence between 4 and 57%. At present is not clear if this toxic effect is due to temozolomide administration or to the frequent corticosteroid co-medications used as anti cerebral oedema [35,44].…”
Section: Myelosuppressionmentioning
confidence: 97%
“…Combination therapy with multiple chemotherapeutic drugs known to deplete MGMT (specifically procarbazine and temozolomide) has been successfully assessed in a Phase I trial 27 but as yet has not been shown to confer a benefit in survival. O 6 benzylguanine (O 6 BG), a substrate for MGMT has also been used to decrease MGMT levels.…”
Section: Mgmtmentioning
confidence: 99%